Mayadevi Temple: Recent Discovories and its Implications on History of Building at Lumbini - Tiwari, Sudarshan Raj (Tribhuvan University Journal, 2010)
Not available. Key words: Discovories; History of Building; Lumbini Tribhuvan University Journal Vol. XIX, 1996 Page: 1-14 Uploaded Date: 22 Nov., 2010